P47 Developing a multi-professional, regional, simulation faculty debriefing course. (5th November 2017) - Lawson, S; Corry, R; Duffy, M; Morrow, M; Traynor, M
Abstract : Simulation-based education (SBE) is a well-established tool in many high-reliability organisations. 1 At a strategic level 'Improving patient safety through multi-disciplinary simulation and human factors training' is an accepted task as part of the Department of Health for Northern Ireland's Quality 2020 Strategy 2 and a key objective is to develop an inter-professional Simulation Faculty Development Programme for Northern Ireland. Methodology: A multi-disciplinary reference group including medical, nursing and ambulance representatives was established. A review of existing courses identified some common themes; an introduction to simulation theory, debriefing skills and scenario development. It was agreed to initially focus on developing a Debriefing Course with permission from the Scottish Centre for Simulation and Clinical Human Factors to base the course on their debriefing model. A working group was established to design the pilot course. To explore potential course content and structure focus groups were held for trainees and structured interviews and observation of medical and nursing facilitators at an established SBE course was undertaken. The pilot course was designed for six participants and offered to facilitators from an established inter-professional undergraduate SBE course. The self-selecting nurse and four medical candidates (second nurse absent due to sickness) completed pre and post course evaluations. We sought information about confidence levels as well as any suggested changes for future courses. All candidates enjoyed the course and felt it met their learning objectives. Comments such as "excellent course", "useful, practical and relevant" and "felt empowered as a nurse" highlighted a successful pilot. Suggestions for improvement included a faculty demonstration of the proposed model and providing a hand-out "to reinforce learning" and as a result pre-course learning was developed for future courses. Results: The four medical and two nursing candidates on the subsequent course completed the same evaluations. Again all enjoyed the course and felt it met their learning objectives. Comments included, "useful and relaxed learning environment" and "thanks for a really informative and interactive day". Confidence levels were assessed on a Likert scale (0–5) and perceived confidence levels in debriefing skills rose from a mean of 2.17 pre-course to 3.75 post-course and confidence in managing the difficult debrief rose from a mean of 1.67 to 3.0. Suggestions for improvement included a "full example of debriefing" and a faculty demonstration will be included in the revised course. Our aim is to use PDSA methodology to continually refine and develop the optimal debriefing skills References: . Donaldson L. Chief medical officer report. Safer Medical Practice: Machines, Manikins and Polo Mints 2008. Department of Health. . Improving patient safety through multi-disciplinary simulation and human factors training. Quality 2020.